Methods of Diagnosing Immunodeficiency in Adolescents - Alkhaliq, Ghufran Qasim Abd; Al-Zubaidi , Argwan M.; Talab , Tabarak J.; Amer , Hala (International Journal Papier Advance and Scientific Review, 2024)
Immunodeficiency disorders in adolescents represent a complex and multifaceted challenge in clinical practice. A timely and accurate diagnosis is crucial for appropriate management and improved patient outcomes. This review paper comprehensively examines the methods employed in diagnosing immunodeficiency disorders in adolescents. We explore clinical assessments, laboratory tests, genetic analyses, imaging techniques, and functional assays, highlighting their respective advantages and disadvantages. A critical understanding of these diagnostic approaches equips healthcare professionals with valuable tools to enhance the healthcare of adolescents with immunodeficiency disorders. Furthermore, some systems for diagnosing diseases that affect immunity are explained.